TRABALHO E SAÚDE: ESTUDO COM TÉCNICOS SOCIAIS DO SISTEMA ÚNICO DE ASSISTÊNCIA SOCIAL. IRATI - Kruger, Gabriel Batista (2016)
This study aims to understand the work of the management of social workers who work in the Specialized Reference Center for Social CREAS assistance, seeking to understand the subjective impact on employees who work with families in vulnerability, reflecting on the resolution capability at work through the relationship between working conditions and mental suffering, and understand the action capacity of professionals regarding working conditions in the public policy of the Unified Social assistance in a group of workers in western Parana downtown area. The initial demand came through the participation of the monthly meetings of workers who are sought in view of the difficulties in managing work. The qualitative research was primary data collection technique to semi-structured individual interviews. Altogether Bostonian interviewed 8 social workers, 1 pedagogue, 6 social workers and 1 psychologist. We used the Clinic of activity - Yves Clot- as theoretical conceptual contribution to discussion of the data. The data revealed that the technicians are subject to casualization at work in terms of material conditions, human resources and lack of training. Such conditions make the social workers feel their activity prevented, do not find the professional resources to gender intervention in work situations. According to the testimony, the conditions and the organization of work in general affect the living conditions and health professionals resulting in somatization and psychosomatic, stress and insomnia. It is concluded that the conditions and the organization of work are crucias elements for the realization of being prevented from working, and be professional genre little cohesive or non-existent, there are resolutions height to defend these aspects and symbolize the tangle which are trapped.